The Role of Practitioner Research in Developing Cultures of Learning in Children and Families Social Work. Issue 3 (26th May 2016) - MacRae, R.; Smith, M.; Cree, V.E.
Abstract : Over the past decade, higher education policy in the United Kingdom has increasingly focused on the impact of academic research with research councils putting out specific calls for knowledge exchange (KE) opportunities. This KE project involved a Scottish university working with practitioners from two Local Authority Children and Families Social Work departments. The aim, in line with the recent UK Government-sponsored review of child protection, was to contribute to effecting a shift from a compliance to a learning culture. This article discusses whether and to what extent academic support for small-scale practitioner research projects delivered as part of a larger KE project can contribute to the development of learning cultures in statutory social work settings. We conclude that while it is difficult to demonstrate this in any absolute sense, the practitioners who took part gained greatly from doing so and have gone on to share their new knowledge and skills with others in their agencies. The relationships between practitioners and academics were central for creating space for critical discourse and KE. The learning from this KE project could usefully inform other knowledge brokerage projects going forward.